Effects of different sodium salts and nitrogen sources on the production of 3-hydroxybutyrate and polyhydroxybutyrate by Burkholderia cepacia . - Wang, Jianfei.; Huang, Jiaqi.; Guo, Huanyu.; Jiang, Shaoming.; Qiao, Jinyue.; Chen, Xingyu.; Qu, Zixuan.; Cui, Wanyue.; Liu, Shijie. (Tufts University. Tisch Library., 2021)
Keywords: 3-Hydroxybutyrate, Polyhydroxybutyrate, Burkholderia cepacia, Sodium salts, Nitrogen source.; Springer Open.